UNSOLVED MYSTERIES: The Disappearance of Madeleine McCann - Koudouna, Antheia; Demiri, Maria (Open Schools Journal for Open Science, 2025)
The disappearance of Madeleine McCann remains one of the most high-profile and mysterious missing child cases in modern history. Despite extensive international investigations and numerous reported sightings, the truth behind her disappearance continues to elude authorities. This presentation explores key aspects of the case, including eyewitness testimonies, timeline discrepancies, and the role of media and forensic evidence. Our aim is to shed light on the known facts and raise awareness about the ongoing efforts and challenges in resolving such tragic and complex cases.